Revision of the genus Harmothoe Kinberg, 1856 (Polychaeta: Polynoidae) in the Northeast Atlantic - Barnich, Ruth; Fiege, Dieter (Zootaxa, 2009)
The type material and original descriptions of 126 nominal species from the Northeast Atlantic originally described as belonging to Harmothoe Kinberg, 1856 or later referred to this genus were examined. Of these species, only 28 are considered to be valid, i.e. less than 25 %, the others being either junior synonyms, indeterminable, invalid, or referred to other genera. The valid species are described and figured, including two new species, H. fernandi n. sp. and H. mariannae n. sp. For H. extenuata (Grube, 1840), H. imbricata (Linnaeus, 1767), and H. impar (Johnston, 1839), neotypes are designated, since their type material is lost and their original descriptions are insufficient. Harmothoe aequespina (Langerhans, 1884) and H. clavigera (M. Sars, 1863) represent new combinations. An illustrated identification key to all valid Harmothoe species of the region is given.